Comparison of Animal Sera for Suitability in Coagulase Testing - Orth, D. S. (1971)
The sera of several animals were examined for suitability in coagulase testing. The assay for coagulase-reacting factor (CRF) activities of the whole sera indicated the following relative concentrations of CRF: human > pig > rabbit > horse > bovine, chicken, and lamb. Human, pig, and rabbit sera had adequate amounts of CRF for coagulase testing. The plasmin activities of the different sera, arranged from the strongest to the weakest, were as follows: rabbit > human > lamb > horse > bovine, chicken, and pig. Fibrinolysis was observed when rabbit, human, lamb, or horse sera were incorporated into coagulase test agars. Pig serum was superior to the other sera for use in the plate test for coagulase since it had adequate amounts of CRF and the plasminogen-plasmin system was not activated by staphylokinase or staphylococcal Müller factor. Heparinized pig plasma was more suitable than citrated pig plasma since citrate interfered with the growth of Staphylococcus aureus, and the use of heparinized plasma prevented false-positive coagulase reactions due to citrate utilization.